Learning to teach citizenship in the secondary school: A companion to school experience - Gearon, L (RoutledgeFalmer, 2003)
Citizenship is a wide-ranging subject that can be taught in its own right, or through other curriculum subjects and activities. This book is intended for students training to teach Citizenship as a first or second subject, and will also be immensely helpful to experienced teachers who have opted to take responsibility for this exciting subject. Written in a clear and practical way, yet underpinned by a sound theoretical background, the book covers key themes in Citizenship education, including: • Citizenship in the National Curriculum • Citizenship and pastoral care • special educational needs • developing schemes of work • ways of teaching and learning • assessment, monitoring and recording • resources and useful contacts • professional development. With key objectives and tasks for each chapter, this book will help teachers to improve their understanding of Citizenship education and to help their pupils understand their roles as citizens. It may be read in conjunction with the companion core textbook, Learning to Teach in the Secondary School, 3rd edition. © 2003 Selection and editorial matter: Liam Gearon. © Individual chapters: the contributors. All rights reserved.